German Industry Succeeds with Research-Intensive Goods - Heike Belitz; Martin Gornig; Alexander Schiersch (Weekly Report, 2010)
As a country highly specialized in the production of investment goods, Germany has been especially hard hit by the global recession. Because the production profile of German industry is technology-intensive, however, there is reason to believe that Germany will emerge from the present economic crisis with renewed strength. In no other industrialized nation is production as heavily geared to research-intensive goods as it is here. Germany has increased its lead over its most significant rivals not only in motor vehicle manufacturing, but also in machinery, communication equipment, and medical and precision instruments. The success of German companies is based not only on compelling products, but also on the relative efficiency of their production processes compared to other countries.
Keywords: O14; O40; O57; 330; Industrial specialisation; Technological change; Technical efficiency